Sequence Context Influences the Structure and Aggregation Behavior of a PolyQ Tract - Eftekharzadeh, Bahareh (Biophys J, 2016)
Expansions of polyglutamine (polyQ) tracts in nine different proteins cause a family of neurodegenerative disorders called polyQ diseases. Because polyQ tracts are potential therapeutic targets for these pathologies there is great interest in characterizing the conformations that they adopt and in understanding how their aggregation behavior is influenced by the sequences flanking them. We used solution NMR to study at single-residue resolution a 156-residue proteolytic fragment of the androgen receptor that contains a polyQ tract associated with the disease spinobulbar muscular atrophy, also known as Kennedy disease. Our findings indicate that a Leu-rich region preceding the polyQ tract causes it to become α-helical and appears to protect the protein against aggregation, which represents a new, to our knowledge, mechanism by which sequence context can minimize the deleterious properties of these repetitive regions. Our results have implications for drug discovery for polyQ diseases because they suggest that the residues flanking these repetitive sequences may represent viable therapeutic targets.